2011
DOI: 10.1136/gutjnl-2011-300721
|View full text |Cite
|
Sign up to set email alerts
|

Generation of gaseous sulfur-containing compounds in tumour tissue and suppression of gas diffusion as an antitumour treatment

Abstract: Gaseous sulfur-containing compounds are the main products in tumours and preventing the diffusion of these compounds reduces the tumour proliferation rate, which suggests the possibility of a new approach to cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
(25 reference statements)
2
36
0
Order By: Relevance
“…Lower levels were found for several (CH x ) x S x compounds, whereas increased levels of other sulfur-containing compounds, like carbon disulfide and 2,4-dithiapentane, were seen in patients with CD and UC compared with HC. Sulfur compounds have been implicated in the onset32 47 and relapse of UC48 but also in the initiation of carcinogenesis 47 49 50. Previously, we showed that mucosal sulfide detoxification mechanisms are decreased in CD and UC 51…”
Section: Discussionmentioning
confidence: 94%
“…Lower levels were found for several (CH x ) x S x compounds, whereas increased levels of other sulfur-containing compounds, like carbon disulfide and 2,4-dithiapentane, were seen in patients with CD and UC compared with HC. Sulfur compounds have been implicated in the onset32 47 and relapse of UC48 but also in the initiation of carcinogenesis 47 49 50. Previously, we showed that mucosal sulfide detoxification mechanisms are decreased in CD and UC 51…”
Section: Discussionmentioning
confidence: 94%
“…There are several lines of prior studies demonstrating that volatile sulfur compounds, including H 2 S, are increased in patients with certain forms of cancer (31,32), although its sources or biological functions remained unexplored. In addition, several prior studies demonstrated an increase in CBS expression in various forms of human cancer (33)(34)(35), although the functional consequence of these observations remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in one prior study, CBS expression has been associated with increased cell proliferation (MacLean et al ., ) (even though none of these prior investigations raised the potential involvement of H 2 S). In addition, several studies demonstrated increased H 2 S production in the exhaled air and flatus of cancer patients (Kumar et al ., ; Yamagishi et al ., ; Altomare et al ., ) and increased urinary excretion of thiosulfate, the stable breakdown product of H2S (Chwatko et al ., ) (even though these investigations have not identified the enzymatic source). Finally, several recent studies noted the inhibitory effect of AOAA on cancer cell proliferation in vitro and/or in vivo (Thornburg et al ., ; Weinberg et al ., ; Anso et al ., ; Son et al ., ) (even though these investigators attributed the effects of AOAA to pharmacological actions other than CBS inhibition).…”
Section: H2s As Endogenously Produced Metabolic ‘Fuel’ In Cancer Cellsmentioning
confidence: 98%